Working on platforms in Argentina: profile, expectations and labor conditions in 2021 - Fernandez Massi, Mariana; Viego, Valentina (Cuadernos de Relaciones Laborales, 2023)
In the last 5 years, digital platforms have increased their participation in the occupational structure around the world. In Argentina, around 8% of the employed population obtain main or secondary income from these devices (Aguilar et al., 2022), a proportion that probably increased after the outbreak of the COVID-19 pandemic and its related sanitary measures. This article describes the arrival of the platforms in Argentina, their penetration in the labor market, the most prevalent branches, the sociodemographic profile of the workers, working conditions, duration of the workday, income, combination with other jobs, tenure and workers´ expectations. The analysis is based on data from Argentina obtained from the Digitrab database, which collects information on active platform workers carried out between April and September 2021. The results of the survey are complemented by in-depth interviews with workers and management personnel and with previous studies.